PERMEABILITY COEFFICIENT OF PERVIOUS CEMENT MORTAR MEASURED BY THE CONSTANT HEAD AND FALLING HEAD METHODS - Yogafanny, Ekha; Triatmadja, Radianta; Nurrochmad, Fatchan; Supraba, Intan (Journal of Applied Engineering Science, 2023)
The modified pervious concrete and cement mortar, known as pervious cement mortar (PCM), is designed with a specific composition to create pores. The coarse aggregate is removed to form smaller pore sizes. PCM acts as a water filter, needing higher permeability than cement mortar but less than pervious concrete. Its pores drain water while trapping impurities. This study compares the effects of sand-to-cement ratio (S/C), specimen thickness, and age on permeability and porosity. It also contrasts PCM’s permeability coefficient determined by constant head and falling head methods. Numerous studies compare permeability coefficients in pervious concrete using these methods, but not for finer aggregate cement-based composite materials like pervious cement mortar. PCM uses fine aggregate (0.6 – 0.85 mm) at 3, 5, and 10 cm thickness with S/C ratios of 4 and 5. Findings show that S/C 5 specimens have significantly higher porosity than S/C 4. The S/C ratios notably impact permeability; the higher ratio means the higher permeability. Permeability coefficients for S/C 4 ranging from 0.006 – 0.075 cm/s, while S/C 5 ranging from 0.010 to 0.147 cm/s. The relationship between the permeability coefficient between the constant head and falling head methods at the age of 90 days specimen are Kc = 1.0516 Kf (S/C 4.2) and Kc = 0.9325 Kf (S/C 5.2). According to these findings, finer aggregates result in a significantly smaller permeability, to the extent that the constant head method is more reliable compared to the falling head method.